Early stimulation in the development of children with microcephaly: maternal perception - Brena Shellem Bessa de Oliveira; Francisca Mayra de Sousa Melo; Rhaiany Kelly Lopes de Oliveira; Joana Furtado de Figueiredo Neta; Flávia Paula Magalhães Monteiro; Emanuella Silva Joventino
ABSTRACT Objective: To know the maternal perception about early stimulation and its repercussion in the development of the child with microcephaly associated with zika virus. Method: A qualitative study was carried out from June to August 2017 with five mothers of children diagnosed with microcephaly associated with zika virus. The data were collected through individual interviews with semi-structured script and evaluated by the content analysis, in its thematic modality. Results: Mothers recognized the benefits and the advances in the development of the child after the beginning of the early stimulation. It is noteworthy that the difficulty of transportation was the main reason for the lack of attendance at consultations, and that the short time of stimulation was the main weakness of the service. Final considerations: The recognition of maternal perception and the difficulties and weaknesses of the service can contribute to the elaboration of public policies and the planning of holistic care for children with microcephaly and their families.